Isolation of Vibrio cholerae from clinical and drinking water samples during Cholera Outbreak in Khairpur Sindh Pakistan - Ali Mughal, Amjad; Faiz Kazi, Yasmeen; Bokhari, Habib (International Journal of Endorsing Health Science Research, 2021)
Background: Cholera is a diarrheal disease that is caused by the bacterium Vibrio cholerae that transmits through contaminated water, food, oral-fecal route and spread through poor sanitation system. This study aims to investigate the reports of clinical and drinking water samples during an epidemic in Pakistan. Methodology: This study was conducted in District Khairpur including 660 samples (360 from clinical and 300 from drinking water) from 2014-2016. All samples were enriched in Alkaline peptone water for 6 hours and then streaked on TCBS agar, incubated at 35ºC for 24 hours. The next day standard microbiological, biochemical, serological techniques were used for the identification of V. cholerae and further identification was performed using PCR. Results: Out of 360 clinical samples, 76(21.11%) were positive for V. cholerae. The species-specific Outer membrane protein W precursor (ompW) gene was amplified and shown at the correct size (588 bp) through agarose gel electrophoresis. The serotyping revealed that the isolates belonged to serogroup Inaba, O1. cholerae O1 strains shown typical El Tor phenotype similar to V. cholerae El Tor strain N16961 (PBR VP+) used as the reference strain in this study. All age groups were affected where the highest onset was seen among those aged 19 years and above. The culture of drinking water (n=300), observed negative on TCBS agar. Conclusion: As far as our knowledge, this is the first time when the presence of V. cholerae El Tor peak has been reported for causing cholera outbreaks in Khairpur Sindh, Pakistan. However, these findings can be used for further investigations and recognizing control measures.